2016
DOI: 10.20396/ideias.v7i1.8649511
|View full text |Cite
|
Sign up to set email alerts
|

Os tempos para o trabalho e para a família na população feminina em áreas metropolitanas brasileiras

Abstract: Resumo: O artigo objetiva discutir aspectos da vida produtiva e reprodutiva feminina, analisando a distribuição do tempo com afazeres domésticos e jornada de trabalho fora de casa, comparando trabalhadoras com filhos e sem filhos, de 16 a 59 anos de idade, residentes em áreas metropolitanas. As informações são provenientes das PNADs 2002 e 2012. Os resultados apontam para a manutenção de uma extensa jornada semanal feminina dedicada tanto ao trabalho doméstico-familiar quanto ao trabalho fora de casa. As mulhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Studies have shown that the official status of the relationship is one of the variables that most differs between women who have had children and women who have not had children in Brazil, showing that among people who have had children, married or in a stable union predominate, while among people who have not had children, single women predominate (Caetano et al, 2016). Although marital status is an important factor in PCM and NCM, this condition seems to have less relevance over the decades for younger individuals (Oliveira & Marcondes, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the official status of the relationship is one of the variables that most differs between women who have had children and women who have not had children in Brazil, showing that among people who have had children, married or in a stable union predominate, while among people who have not had children, single women predominate (Caetano et al, 2016). Although marital status is an important factor in PCM and NCM, this condition seems to have less relevance over the decades for younger individuals (Oliveira & Marcondes, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A partir de 2001, com a incorporação da informação sobre horas dedicadas aos afazeres domésticos na série da PNAD, as análises passaram a atestar o quão desigual eram os tempos masculinos e femininos para o trabalho social, assim como as desigualdades moldadas pela idade, raça/cor, estado conjugal, renda, status reprodutivo, posição ocupada no domicílio e na família e local de residência (BRUSCHINI, 2006;SOUSA;GUEDES, 2016;OLIVEIRA;MARCONDES, 2016).…”
Section: Divisão Sexual Do Trabalho E Uso Do Tempo: Configurações E R...unclassified